Advantages of different dietary supplements for elite combat sports athletes: a systematic review and Bayesian network meta-analysis - Luo, H.; Tengku Kamalden, T. F.; Zhu, X.; Xiang, C.; Nasharuddin, N. A. (Scientific Reports, 2025)
With an increasing number of studies delving into the impact of dietary supplements on combat sports performance, researchers are actively seeking a more efficient dietary supplement for use in these sports. Nonetheless, controversies persist. Hence, we undertook a systematic review and Bayesian network meta-analysis to discern the most effective dietary supplements in combat sports by synthesizing the available evidence. We conducted a comprehensive search across PubMed, Web of Science, Cochrane, Embase, and SPORTDiscus, covering the period from their establishment to November 2, 2023. Our aim was to identify randomized controlled trials that evaluated the benefits of various dietary supplements for elite combat sports athletes. The risk of bias in these trials was assessed using the revised Cochrane Risk of Bias Tool for Randomized Trials. Subsequently, we employed Bayesian network meta-analysis through R software and Stata 15.0. During the analysis, we performed subgroup analysis based on the type of combat, distinguishing between striking and grappling disciplines. The analysis is based on 67 randomized controlled trials that meet all the inclusion criteria, involving 1026 elite combat sports athletes randomly assigned to 26 different dietary supplements or placebos. Results from the 50 trials included in the network meta-analysis indicate that compared to a placebo, sodium bicarbonate combined with caffeine (SMD: 2.3, 95% CrI: 1.5, 3.2), caffeine (SMD: 0.72, 95% CrI: 0.53, 0.93), beta-alanine (SMD: 0.58, 95% CrI: 0.079, 1.1), and sodium bicarbonate (SMD: 0.54, 95% CrI: 0.30, 0.81) was associated with a statistically significant increase in blood lactate concentrations. Compared to placebo, caffeine (SMD: 0.27, 95% CrI: 0.12, 0.41) was associated with a statistically significant increase in the final heart rate. Compared to placebo, creatine combined with sodium bicarbonate (SMD: 2.2, 95% CrI: 1.5, 3.1), creatine (SMD: 1.0, 95% CrI: 0.38, 1.6), and sodium bicarbonate (SMD: 0.42, 95% CrI: 0.18, 0.66) was associated with a statistically significant increase in mean power. Compared to placebo, creatine combined with sodium bicarbonate (SMD: 1.6, 95% CrI: 0.85, 2.3), creatine (SMD: 1.1, 95% CrI: 0.45, 1.7), and sodium bicarbonate (SMD: 0.35, 95% CrI: 0.11, 0.57) was associated with a statistically significant increase in peak power. Compared to placebo, caffeine (SMD: 1.4, 95% CrI: 0.19, 2.7) was associated with a statistically significant increase in the number of kicks. Compared to placebo, caffeine (SMD: 0.35, 95% CrI: 0.081, 0.61) was associated with a statistically significant increase in the number of throws. This study suggests that a range of dietary supplements, including caffeine, sodium bicarbonate, sodium bicarbonate combined with caffeine, creatine, creatine combined with sodium bicarbonate, and beta-alanine can improve the athletic performance of elite combat sports athletes.